2020
DOI: 10.3390/su13010275
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Green Creativity for Employees in Green Enterprises: Scale Development and Validation

Abstract: Although employee green creativity is recognized as the key to the innovation in green enterprises, few studies explores the measurement of green creativity for employees. To address the gap, the present study identifies the major dimensions of employee green creativity and develops a comprehensive, reliable, and valid measurement instrument. According to the 4P’s model of creativity, four core dimensions of employee green creativity are identified, namely, green creative motivation, thinking, behavior, and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…The recent studies have shown that green creativity is positively correlated to the performance of developing green products and achieving environmental sustainability. The aim of this phenomenon is to reduce the negative impacts on the environment by the organisations so as to achieve their primary purpose, i.e., social responsibility and provide benefits to the society and the organisation which in turn improve their environmental performance (Jiang et al, 2020;Al-Talibi et al, 2021).…”
Section: Green Creativitymentioning
confidence: 99%
See 3 more Smart Citations
“…The recent studies have shown that green creativity is positively correlated to the performance of developing green products and achieving environmental sustainability. The aim of this phenomenon is to reduce the negative impacts on the environment by the organisations so as to achieve their primary purpose, i.e., social responsibility and provide benefits to the society and the organisation which in turn improve their environmental performance (Jiang et al, 2020;Al-Talibi et al, 2021).…”
Section: Green Creativitymentioning
confidence: 99%
“…Several researchers referred to a group of dimensions (Jiang et al, 2020;Maitlo et al, 2022;Li et al, 2020):…”
Section: Dimensions Of Green Creativitymentioning
confidence: 99%
See 2 more Smart Citations
“…Green human resource management may promote the sustainability of enterprises as an essential technique for influencing the green behavior of employees ( Amjad et al, 2021 ; Zhu et al, 2021 ). Employee green creativity is regarded as the driving force behind company green innovation, and employee green behavior is a crucial metric for measuring employee green creativity ( Jiang et al, 2020 ). Gaudencio et al (2017) found that CSR increases employee job satisfaction and organizational commitment and has a beneficial effect on the establishment of a stable innovation team ( Ho, 2017 ).…”
Section: Literature Reviews and Research Hypothesesmentioning
confidence: 99%